AGGRESSIVENESS, PESANTREN AND SHIYAM (A COMPARATIVE STUDY) - Fitriyah Fitriyah; Falasifatul Falah (Proyeksi: Jurnal Psikologi, 2012)
Aggressive behaviors by adolescents in Indonesia has perceived as national problem. This problem ofbehavior occur among all background of teenagers, including young people who had religiousbackground. There are two purposes of the study: 1). To examine the difference of aggressivenessbetween adolescent living in pesantren and adolescent living outside pesantren; and 2). To examine thedifference of aggressiveness among adolescents doing different frequency of religious fasting (shiyam),especially non-obligatory (sunnah) fasting on Monday or Thursday. The population of study was 11 to 21years old male-Moslem adolescent living in Kelurahan Bangunharjo, Semarang. Samples of study takenwith random sampling, based on data of residences in Kelurahan Bagunharjo Semarang. Twohypotheses were proposed in this study: 1). There are different aggressiveness between adolescentsliving in pesantren and ones living outside of pesantren; and 2). There are different aggressivenessamong adolescents doing different frequencies of Monday-Thursday shiyam. The first examinationemploying independent sample t-test resulted in t=-4,902 which p=0,00 (p<0,01), showed that the firsthypothesis was proved: there was a very significant difference of aggressiveness between the group ofMuslim-male adolescents living in pesantren and the group of others, the first group showed loweraggressiveness. The second examination employing one-way anova resulted in F=16,736 which p=0, 00(p<0, 01), showed that the second hypothesis was also proved: there was a very significant difference ofaggressiveness among the groups of Muslim-male adolescents with different frequency of religiousfasting (shiyam): the more frequency of religious fasting, the lower aggressiveness was. The result ofstudy suggested that both religious living environment and religious fasting might give contribution todecrease aggressiveness on adolescents.